Levoglucosan and phenols in Antarctic marine, coastal and plateau aerosols - ZANGRANDO, Roberta; BARBARO, ELENA; VECCHIATO, MARCO; KEHRWALD, NATALIE MARIE; BARBANTE, Carlo; GAMBARO, Andrea (Science of The Total Environment, 2016)
Due to its isolated location, Antarctica is a natural laboratory for studying atmospheric aerosols and pollution in remote areas. Here, we determined levoglucosan and phenolic compounds (PCs) at diverse Antarctic sites: on the plateau, a coastal station and during an oceanographic cruise. Levoglucosan and PCs reached the Antarctic plateau where they were observed in accumulation mode aerosols (with median levoglucosan concentrations of 6.4pgm-3 and 4.1pgm-3, and median PC concentrations of 15.0pgm-3 and 7.3pgm-3). Aged aerosols arrived at the coastal site through katabatic circulation with the majority of the levoglucosan mass distributed on larger particulates (24.8pgm-3), while PCs were present in fine particles (34.0pgm-3). The low levoglucosan/PC ratios in Antarctic aerosols suggest that biomass burning aerosols only had regional, rather than local, sources. General acid/aldehyde ratios were lower at the coastal site than on the plateau. Levoglucosan and PCs determined during the oceanographic cruise were 37.6pgm-3 and 58.5pgm-3 respectively. Unlike levoglucosan, which can only be produced by biomass burning, PCs have both biomass burning and other sources. Our comparisons of these two types of compounds across a range of Antarctic marine, coastal, and plateau sites demonstrate that local marine sources dominate Antarctic PC concentrations.